PERAN KEPEMIMPINAN DIRI DALAM MEMBANGUN TIM DI UPTD TAHURA BUKIT SOEHARTO - Salsabila, Nada; Eka Wardhana, Kautsar (Universitas Nahdlatul Ulama Kalimantan Timur, 2024)
This research was carried out to uncover and understand the role of self-leadership in the team-building process at UPTD Tahura Bukit Soeharto using a descriptive qualitative approach. The research subjects and main data sources focused on the head of UPTD Tahura Bukit Soeharto and the forestry police team. Various techniques applied to collect data were interviews, observations, and documentation.The result showed that in the context of self-leadership and team-building efforts at UPTD Tahura Bukit Soeharto, the head of UPTD applied five sources of strength namely personal strength, knowledge, relationships, influence and resources. This shows that leadership strength does not depend on the position or title, but rather on how a leader utilizes the various strengths to inspire, motivate, and build a solid team.Furthermore, when facing various challenges faced by the team, the head of UPTD Tahura Bukit Soeharto acts as a leader who provides emotional support to his members and encourages flexibility, which contributes to increasing the team's resilience. This results in team members feeling more secure and supported, so they can deal with difficult situations and find innovative solutions. With this support, a strong bond is created between team members, which is important for maintaining enthusiasm and motivation in achieving common goals.